INFLUENCE OF THE TIMING OF HIP FRACTURE SURGERY ON FINAL TREATMENT OUTCOMES - Dabetic, Uros; Grupković, Jovana; Zagorac, Slavisa; Simić, Marko; Tulić, Goran (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Globally, the incidence of hip fractures has had an increasing trend, due to longer life expectancy. It is estimated that, by 2050, it will have reached 6.26 million cases a year. The aim of our review is the analysis of available literature on the relationship between the timing of hip fracture surgery and its impact on morbidity and mortality. Results: Over 85% of patients who suffer hip fracture are individuals older than 65 years with existing comorbidities. Even with adequate and optimal treatment, age and comorbidities predispose these patients to a worse prognosis and higher morbidity and mortality, as compared to the general population. The official position of AAOS is that patients who are operated on within 48 hours of hospital admission have a better treatment outcome. The reasons for delaying surgical treatment can be divided into medical and nonmedical. A large number of published studies support the claim that patients who are operated on 24 hours within hospital admission have a better outcome in terms of complications and mortality (after 30 days and after one year) than patients who are operated on later. On the other hand, several retrospective studies and meta-analyzes have shown that there is no significant difference in mortality between patients operated on 24 h, 36 h, and 48 h after admission. However, in these studies, surgical treatment within 4 days of admission has been identified as the most significant factor correlating with reduced mortality. Conclusion: Patients with hip fractures should be operated on within 24 hours of admission unless they have an acute medical condition that prevents surgery. If there is a medical condition that can be corrected, this window is prolonged to 48 hours, but the waiting time for surgical treatment should not be longer than 4 days.